SiGe layer thickness effect on the structural and optical properties of well-organized SiGe/SiO2 multilayers - Vieira, E. M. F. (2017)
In this work, we report on the production of regular (SiGe/SiO2)20 multilayer structures by conventional RF-magnetron sputtering, at 350 °C. Transmission electron microscopy, scanning transmission electron microscopy, raman spectroscopy, and x-ray reflectometry measurements revealed that annealing at a temperature of 1000 °C leads to the formation of SiGe nanocrystals between SiO2 thin layers with good multilayer stability. Reducing the nominal SiGe layer thickness (t SiGe) from 3.5-2 nm results in a transition from continuous SiGe crystalline layer (t SiGe ∼ 3.5 nm) to layers consisting of isolated nanocrystals (t SiGe ∼ 2 nm). Namely, in the latter case, the presence of SiGe nanocrystals ∼3-8 nm in size, is observed. Spectroscopic ellipsometry was applied to determine the evolution of the onset in the effective optical absorption, as well as the dielectric function, in SiGe multilayers as a function of the SiGe thickness. A clear blue-shift in the optical absorption is observed for t SiGe ∼ 2 nm multilayer, as a consequence of the presence of isolated nanocrystals. Furthermore, the observed near infrared values of n = 2.8 and k = 1.5 are lower than those of bulk SiGe compounds, suggesting the presence of electronic confinement effects in the nanocrystals. The low temperature (70 K) photoluminescence measurements performed on annealed SiGe/SiO2 nanostructures show an emission band located between 0.7-0.9 eV associated with the development of interface states between the formed nanocrystals and surrounding amorphous matrix.